2021
DOI: 10.3389/fpls.2021.792384
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Morphology, Chemical Compositions, and the Biosynthesis Regulations of Cuticle in Response to Chilling Injury of Banana Fruit During Storage

Abstract: The plant cuticle covers almost all the outermost surface of aerial plant organs, which play a primary function in limiting water loss and responding to the environmental interactions. Banana fruit is susceptible to thermal changes with chilling injury below 13°C and green ripening over 25°C. Herein, the changes of surface morphology, chemical compositions of cuticle, and the relative expression of cuticle biosynthesis genes in banana fruit under low-temperature storage were investigated. Banana fruit exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Rahman et al ( 2021 ) have examined the role of cuticular waxes in reducing low temperature and dehydration stresses in Arabidopsis mutants and transgenic plants with altered cuticular wax formation, and found that cuticular alkane waxes, along with alcohols and fatty acids, promote the avoidance of both ice formation and leaf water loss under dehydration stress. Banana fruit are sensitive to thermal changes, with cold injury at temperatures below 13 °C and green ripening at temperatures above 25 °C (Huang et al 2021 ). Changes in surface structure, cuticle chemical composition, and relative expression of cuticle biosynthesis genes in banana fruit during cold storage show that the contents of fatty acids and aldehydes in cuticular wax tend to increase with cold injury (Huang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al ( 2021 ) have examined the role of cuticular waxes in reducing low temperature and dehydration stresses in Arabidopsis mutants and transgenic plants with altered cuticular wax formation, and found that cuticular alkane waxes, along with alcohols and fatty acids, promote the avoidance of both ice formation and leaf water loss under dehydration stress. Banana fruit are sensitive to thermal changes, with cold injury at temperatures below 13 °C and green ripening at temperatures above 25 °C (Huang et al 2021 ). Changes in surface structure, cuticle chemical composition, and relative expression of cuticle biosynthesis genes in banana fruit during cold storage show that the contents of fatty acids and aldehydes in cuticular wax tend to increase with cold injury (Huang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Banana fruit are sensitive to thermal changes, with cold injury at temperatures below 13 °C and green ripening at temperatures above 25 °C (Huang et al 2021 ). Changes in surface structure, cuticle chemical composition, and relative expression of cuticle biosynthesis genes in banana fruit during cold storage show that the contents of fatty acids and aldehydes in cuticular wax tend to increase with cold injury (Huang et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…And these thermal differences on the surface of the fruits, which are significant indexes in the fruit industry can be delicately captured by the fruit temperature sensor, indicating its promise to reduce production losses and improve fruit quality. [ 65–67 ]…”
Section: Resultsmentioning
confidence: 99%
“…And these thermal differences on the surface of the fruits, which are significant indexes in the fruit industry can be delicately captured by the fruit temperature sensor, indicating its promise to reduce production losses and improve fruit quality. [65][66][67] Generally, the fruit grows slowly at the beginning, and then gradually accelerates. When it reaches the highest point, it gradually slows down and stops growing.…”
Section: Applications On Fruit Surfacementioning
confidence: 99%
“…Bananas are a representative climacteric fruit that is widely cultivated in tropical, subtropical climates and is one of the most consumed fruits for their sweet tastes and flavors in the world. , Since bananas have respiration and ethylene production rates much higher than those of other fruits after harvest, they can show rapid ripening–senescence phenotypes. Due to the release of ethylene gas and the weak physical properties, they are easily softened and damaged by physical pressure and chilling injuries . Recently, the need for biodegradable packaging materials has been growing in the storage of fruits to increase shelf-life.…”
Section: Introductionmentioning
confidence: 99%